The first revelation in the Holy Qur'an : it's significance in the methods of learning / Mashita Abu Hasan - Abu Hasan, Mashita (UPENA, 2005)
This writing is a discussion pertaining to the first revelation i.e. Surah al-Alaq particularly on its first five verses. This study comprises the significance of Surah al-Alaq, its exegesis and prominent commentaries from the mufassirun. The fundamental method of learning such as reading, writing and memorizing in the context of the Surah will also be discussed. The 'qalam' which is known as an important medium of learning, teaching and spreading knowledge is also elaborated in the discussion.